2019
DOI: 10.1080/19476337.2019.1575474
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcus lactissubsp.lactisisolated from fermented milk products and its antimicrobial potential

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Lactococcus lactis subsp. lactis isolated from fermented milk products and its antimicrobial potential

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Several, studies have reported that the Lactobacillus strains exhibited significant antibacterial activities via the production of metabolites, competition with nutrients utilization, and inhibition of bacterial adhesion to the mucosa and improve the immune response [26,27]. In vitro studies also suggested that Lactobacillus lactis exhibited strong antibacterial activities against E. coli, S. aureus, P. aeruginosa, S. typhimurium and E. faecalis [41,42]. The CFS of RWP-3 and RWP-7 exhibited significant antibacterial activity against tested pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Several, studies have reported that the Lactobacillus strains exhibited significant antibacterial activities via the production of metabolites, competition with nutrients utilization, and inhibition of bacterial adhesion to the mucosa and improve the immune response [26,27]. In vitro studies also suggested that Lactobacillus lactis exhibited strong antibacterial activities against E. coli, S. aureus, P. aeruginosa, S. typhimurium and E. faecalis [41,42]. The CFS of RWP-3 and RWP-7 exhibited significant antibacterial activity against tested pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Lactis biovar diacetyactis are used for the production of fermented milk products. L. lactis cremoris is particularly preferred for the production of cheese [ [10] , [11] , [12] ]. Exposure to unpasteurized dairy products has been suggested as a risk factor for L. lactis cremoris infection [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common bacteria used as probiotics are Lactic Acid Bacteria (Dinçer and Kıvanç 2021). Organic acids produced by LAB, hydrogen peroxide, bacteriocin and other antimicrobial properties of synthesized substances prevent the development of undesired microorganisms and pathogens in food (Akbar et al 2019).…”
Section: Introductionmentioning
confidence: 99%